Dispensing Digital Justice: COVID-19, Courts, and the Potentially Diminishing Role of Jury Trials - Bertrand, Michelle I.; Ireland, David; Jochelson, Richard; Kerr-Donohue, Kathleen; Hall, Robson (Interdisciplinary Justice Research, 2021)
Courts around the world moved quickly in determining how to conduct proceedings remotely in response to COVID-induced shutdowns. However, both implicitly and by their actions, in the initial wake of pandemic closures Canadian courts demonstrated a consensus that jury trials could only be conducted in person, even as other proceedings moved to a digital realm. We provide a snapshot of what Canadian courts’ initial responses were in adapting to their new reality. We then highlight general issues that need to be considered in conducting court proceedings online, as well as describe issues specific to criminal jury trials. Our contention is that the failure of Canadian courts to address these issues, and their failure to make any considerations towards conducting jury trials remotely despite doing so for nearly all other proceedings, leaves the jury trial vulnerable to obsolescence in a digital world.